Promoting value-oriented consumer behavior among millennials: The mediating role of attitudes toward sales promotion techniques in economic empowerment initiatives - Jeremia Tiga Parulian; Rizal Edy Halim (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Limited marketing literacy among youth often hinders the development of micro-enterprises and community-based entrepreneurship. To address this challenge, a community service initiative was carried out to educate young entrepreneurs on value-based sales promotion, particularly focusing on the strategic use of discounts. This study aims to evaluate the impact of educational outreach on sales promotion techniques—grounded in utilitarian motivation—on attitude change and behavioral intentions among youth within a local entrepreneurship community in urban Indonesia. Methods: The program involved interactive workshops for 50 youth participants from a community of aspiring entrepreneurs. The impact of the training was assessed through a quantitative approach using Structural Equation Modeling (SEM) to examine the relationships between utilitarian motivation, attitudes toward promotional techniques, and entrepreneurial behavioral intentions. Findings: The results revealed that education on discount-based promotion significantly improved participants’ strategic understanding of value-driven marketing. Positive attitudes toward promotion techniques were found to mediate the influence of utilitarian motivation on the intention to start and grow a business. Conclusion: alue-based promotion education serves as an effective community empowerment strategy to enhance marketing literacy and economic resilience among youth. The program offers a replicable model for strengthening community business capacity and promoting sustainable livelihoods through practical marketing knowledge. Novelty/Originality of this article: This study offers a novel contribution to community service literature by integrating consumer behavior theory into entrepreneurship education for youth empowerment. It bridges academic insight and practical outreach to foster inclusive, sustainable economic development at the grassroots level.